Determination of bacterial contamination of milk using fluorometry (Baghdad Science Journal, 2011)
The aim of this paper is to determine the feasibility of using fluorometric methods as an indicator for quality and contamination of milk with E.coli bacteria, and selection the suitable wavelength to be used with laser induced auto fluorescence. Three groups of milk samples were used in this study: Fresh pasteurized milk samples, milk samples containing different concentration of E.coli bacteria which were added artificially, and milk samples that were kept in refrigerator for 3-5 days. Thirteen excitation wavelengths were used to get the emission spectra for all milk samples using spectroflourometer .The results showed that the emission spectra at 275nm excitation wavelength gave a good differentiation between these three groups. The data analysis demonstrated that the proposed method can bring progress in identification of milk quality and contamination with rapidness, high sensitivity and low cost diagnostic tool. Laser light at this wavelength that transmitted by optical fiber can be used for milk samples examination in situe and for more precise results.